INDEKS EKOLOGI DAN STATUS KONSERVASI LEPIDOPTERA DAN ODONATA PADA EKOSISTEM RIPARIAN DESA LAMSEUNIA KECAMATAN LEUPUNG KABUPATEN ACEH BESAR - Al Hayati, Iyonnas; Nanda, Rizki; Harina Roza, Zultira; Azkia, Umruul (KENANGA : Journal of Biological Sciences and Applied Biology, 2025)
The riparian forest in Lamseunia Village, Aceh Besar, is an important ecosystem that supports biodiversity, including insects such as butterflies (Lepidoptera) and dragonflies (Odonata). This study aims to analyze the diversity and abundance of both groups of insects, as well as their relationship with environmental conditions. The sampling method was carried out directly (hand collection) and using insect nets at three observation stations in November 2023. Data analysis was conducted using ecological indices and RStudio software. The results showed the discovery of 13 species of Lepidoptera from 4 families (Nymphalidae, Pieridae, Papilionidae, Lycaenidae) and 3 species of Odonata from the Libellulidae family. The Shannon-Wiener diversity index (H'=2,226) indicates a moderate level of diversity with an even distribution (evenness=0,95), while the dominance index is low (D=0,115) reflecting a balanced community. The dragonfly Orthetrum sabina was the most dominant due to its adaptability, while the butterfly Graphium sarpedon was the least abundant due to limited host plants. Rarefaction and extrapolation curve analysis (iNEXT) showed potential for additional species richness, especially at station 2. Environmental factors such as temperature (29,3-30,2°C), humidity (62%), and soil pH (6,0-6,5) also influenced insect distribution. Six species (Ideopsis vulgaris, Eurema hecabe, Graphium sarpedon, Orthetrum sabina, Pantala flavescens, and Rhodothemis rufa) are classified as Least Concern (IUCN), but habitat protection is still needed. These results provide baseline data for long-term ecological monitoring and conservation management based on local biodiversity. Keywords : ecological index, conservation status, Lepidoptera, Odonata, riparian ecosystem Lamseunia